Edukasi Strategi Pendayagunaan ZISWAF untuk Kemandirian Ekonomi Jamaah di Pondok Pesantren Mambaul Ulum Al-Birowi - Aldi Khusmufa Nur Iman; Hawa Gazani; Clara Devy Yulvia Ratna Sary; Afaful Ummah; Afuza Medina (Keris: Journal of Community Engagement, 2026)
Mosques have significant potential for the socio-economic empowerment of the community through the instruments of Zakat, Infaq, Sadaqah, and Waqf (ZISWAF). However, in reality, the management of these funds is often passive and consumptive, mostly allocated for physical maintenance. This community service activity aims to provide education and formulate a strategic framework for "Masjid Berdaya, Umat Berkarya" to transform ZISWAF management into productive empowerment at Pondok Pesantren Mambaul Ulum Al-Birowi, Sokobanah District, Sampang Regency. The method used is Participatory Action Research (PAR) involving 50 participants, consisting of Islamic boarding school administrators, mosque takmirs, and local residents. The activity was carried out in five stages: problem identification, planning, implementation, reflection and evaluation, and further development. The results indicated a paradigm shift and a quantitatively significant increase in understanding among the participants. Based on the evaluation, the average pre-test score of participants with a good understanding (categorized as 'Understand' and 'Strongly Understand') of productive ZISWAF strategies was only 13.5%. After the training, the post-test results revealed a drastic improvement, with the average comprehension score reaching 85% (reflecting an overall increase of 71.5%). Specifically, the understanding levels increased regarding the urgency of productive infaq (from 10% to 80%), the distribution of Qardhul Hasan/interest-free loans (from 4% to 80%), the establishment of UMKM bazaars (from 20% to 90%), and the transparency of financial reports (from 20% to 90%). In conclusion, this mentoring program is proven effective in encouraging the partners' commitment to adopt progressive mosque governance to realize the economic independence of the community.